A Technique: Exposure Therapy - Serkan AKKOYUNLU; M. Hakan TÜRKÇAPAR (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Introduction: Exposure with response prevention is an effective treatment for all anxiety disorders. According to the behavioral learning theories, fears which are conditioned via classical conditioning are reinforced by respondent conditioning. Avoidance and safety seeking behaviors prevent disconfirmation of anxious beliefs. In exposure client faces stimulates or cues that elicit fear or distress, by this avoidance is inhibited. Clients are also encouraged to resists performing safety seeking behaviors or rituals that they utilize to reduce fear or distress. Accomplishing these habituation or extinction is achieved. In addition to this clients learn that feared consequences does not realize or not harmful as they believed by experiencing. Emotional processing is believed to be the mechanism of change in exposure. Objective: The aim of this review is to provide a definition of exposure and its effectiveness briefly, and describe how to implement exposure, its steps and remarkable aspects using. Exposure therapies and treatments that involve exposure are proved to be effective in all anxiety disorders. Exposure therapy can be divided in three parts: Assessment and providing a treatment rationale, creating an exposure hierarchy and response prevention plan, implementing exposure sessions. Clients must also continue to perform exposure between sessions. Therapy transcripts are also provided to exemplify these parts. Conclusion: Exposure with response prevention is a basic and effective technique. Every cognitive behavior therapist must be able to implement this technique and be cognizant of pearls of this procedure. (Journal of Cognitive Behavioral Psychotherapy and Research 2013, 2: 121-128) [JCBPR 2013; 2(2.000): 121-128]